2017
DOI: 10.1007/s00068-017-0819-1
|View full text |Cite
|
Sign up to set email alerts
|

Basic echocardiography for undergraduate students: a comparison of different peer-teaching approaches

Abstract: Using different peer-teaching concepts proved to be effective in teaching basic echocardiography. Gender does not seem to have an impact on effectiveness of the instructional approach. Qualitative analysis revealed limited acceptance of peer teaching and especially of video-based instruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 31 publications
4
34
0
Order By: Relevance
“…Most of the included studies were conducted in Germany ( n = 10). Four studies with 3 or 4 study arms were included ( Gradl-Dietsch et al, 2018 ; Herrmann-Werner et al, 2013 ; Münster et al, 2016 ; Ruesseler et al, 2019 ). In these cases, study arms investigating Peyton’s teaching approach or a standard teaching approach were included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the included studies were conducted in Germany ( n = 10). Four studies with 3 or 4 study arms were included ( Gradl-Dietsch et al, 2018 ; Herrmann-Werner et al, 2013 ; Münster et al, 2016 ; Ruesseler et al, 2019 ). In these cases, study arms investigating Peyton’s teaching approach or a standard teaching approach were included.…”
Section: Resultsmentioning
confidence: 99%
“…Study arms using an intervention not eligible for inclusion were excluded from this review. For example, Gradl-Dietsch et al (2018) reported 4 study arms. The study arms peer teaching and peer teaching using Peyton's teaching approach were included.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the included studies were conducted in Germany (n=10). Four studies with or study arms were included (Gradl-Dietsch et al 2018;Herrmann-Werner et al 2013;Münster et al 2016;Ruesseler et al 2019). In these cases, study arms investigating Peyton's teaching approach or a standard teaching approach were included.…”
Section: Included Studiesmentioning
confidence: 99%
“…The study of Herrmann-Werner et al (2013) used a best practice skills laboratory, which consisted of structured individual feedback, performance on manikins and Peyton's teaching approach supervised by student tutors. Three studies (Gradl-Dietsch et al 2019; Gradl-Dietsch et al 2018; Münster et al 2016) used peer or student teachers for the teaching events and Ruesseler et al (2019) used a video 4-step approach.The teaching approach in the control groups was described as traditional Halsted teaching(Balafoutas et al 2019;Romero et al 2018), peer teaching or student tutors teaching(Gradl- Dietsch et al 2019;Gradl-Dietsch et al 2018;Herrmann-Werner et al 2013;Münster et al 2016), 2-stage teaching approach(Jenko et al 2012), Orde's 2-step method(Lapucci et al 2018;Orde et al 2010), standard instructions(Gradl-Dietsch et al 2016;Krautter et al 2011), traditional bedside teaching…”
mentioning
confidence: 99%